إتفاقية المياه: 30 عاماً من التأثير والإنجاز على أرض الواقع - United Nations Economic Commission for Europe (United Nations, 2024)
The year 2022 marks the 30th anniversary of the Convention on the Protection and Use of Transboundary Watercourses and International Lakes (Water Convention), which was adopted in Helsinki in 1992. Showcasing concrete success stories of the Water Convention’s impact on the ground, this publication serves as an important resource to exemplify the benefits of transboundary water cooperation. Readers will better understand the Water Convention’s social, economic and environmental impact as well as its benefits for peace and security in different regional settings over the past three decades.